Il nazional-fascismo economico del giovane Franco Modigliani - MICHELINI, LUCA (Studi e saggi, 2019)
Il nazional-fascismo economico del giovane Franco Modigliani. This volume is the first to reconstruct the intellectual profile of the young Franco Modigliani, who adheres to the economic and political theories of fascism by proposing avant-garde reflections on central issues of the theoretical debate: Keynesian thought, causes and remedies for the Great Crisis of 1929 , theoretical and historical reasons behind economic nationalism and fascist autarchy. After adhering to the theories of spiritual racism, Modigliani was surprised by the promulgation of the anti-Jewish laws of 1938. After arriving in the USA, Modigliani put aside the fascist and nationalist ideology, but he cultivated the study of Keynesian structures and thoughts, of which he then offered an interpretation which is still successful worldwide to the present day.